Short-term seasonal development of anthropometry, body composition, physical fitness, and sport-specific performance in young Olympic weightlifters - Chaabene, H.; Prieske, O.; Lesinski, M.; Sandau, I.; Granacher, U. (Sports, 2019)
The aim of this study is to monitor short-term seasonal development of young Olympic weightlifters` anthropometry, body composition, physical fitness, and sport-specific performance. Fifteen male weightlifters aged 13.2 ± 1.3 years participated in this study. Tests for the assessment of anthropometry (e.g., body-height, body-mass), body-composition (e.g., lean-body-mass, relative fat-mass), muscle strength (grip-strength), jump performance (drop-jump (DJ) height, countermovement-jump (CMJ) height, DJ contact time, DJ reactive-strength-index (RSI)), dynamic balance (Y-balance-test), and sport-specific performance (i.e., snatch and clean-and-jerk) were conducted at different time-points (i.e., T1 (baseline), T2 (9 weeks), T3 (20 weeks)). Strength tests (i.e., grip strength, clean-and-jerk and snatch) and training volume were normalized to body mass. Results showed small-to-large increases in body-height, body-mass, lean-body-mass, and lower-limbs lean-mass from T1-to-T2 and T2-to-T3 (Delta0.7-6.7%; 0.1 = d = 1.2). For fat-mass, a significant small-sized decrease was found from T1-to-T2 (Delta13.1%; d = 0.4) and a significant increase from T2-to-T3 (Delta9.1%; d = 0.3). A significant main effect of time was observed for DJ contact time (d = 1.3) with a trend toward a significant decrease from T1-to-T2 (Delta-15.3%; d = 0.66; p = 0.06). For RSI, significant small increases from T1-to-T2 (Delta9.9%, d = 0.5) were noted. Additionally, a significant main effect of time was found for snatch (d = 2.7) and clean-and-jerk (d = 3.1) with significant small-to-moderate increases for both tests from T1-to-T2 and T2-to-T3 (Delta4.6-11.3%, d = 0.33 to 0.64). The other tests did not change significantly over time (0.1 = d = 0.8). Results showed significantly higher training volume for sport-specific training during the second period compared with the first period (d = 2.2). Five months of Olympic weightlifting contributed to significant changes in anthropometry, body-composition, and sport-specific performance. However, hardly any significant gains were observed for measures of physical fitness. Coaches are advised to design training programs that target a variety of fitness components to lay an appropriate foundation for later performance as an elite athlete.